Voice of Struggle: Portraying Students’ Experiences in Master’s Thesis Writing - Herman Meyer; Sofia Benedic; Ingrid Tanasale; Fredi Meyer (ITScience (Information Technology and Science), 2026)
This study explored the experiences of postgraduate students in preparing a master’s thesis in the English Education Study Program at Pattimura University. The research aimed to investigate students’ perceptions, feelings, challenges, and coping strategies during thesis writing. A qualitative design using a single-case study approach was employed. Three postgraduate graduates who had completed their theses were selected through purposive sampling. Data were collected through semi-structured interviews based on Seidman’s (2006) three-series interview model and analyzed using thematic analysis by Braun and Clarke (2006). The findings showed that thesis writing was a complex academic and emotional process. Three major themes emerged: individual perspectives, psychological aspects, and time management perspectives. Students viewed thesis writing as both meaningful and difficult because it improved their academic skills, emotional resilience, and personal growth. They experienced anxiety, stress, and overthinking, fear of failure, emotional exhaustion, and physical fatigue. Internal and external challenges included low self-confidence, difficulties with academic writing, limited communication with supervisors, a lack of academic resources, technical issues, and environmental distractions. To overcome these problems, students applied coping strategies such as self-regulation, emotional control, time management, goal setting, social support, and maintaining consistent writing habits, which contributed to successful thesis completion and enhanced academic persistence.